Investigation of DCP and SSG as alternative methods to determine subgrade stability - Sawangsuriya, Auckpath; Edil, Tuncer (Wisconsin Highway Research Program, 2005)
The use of the soil stiffness gauge (SSG) and dynamic cone penetrometer (DCP) for earthwork property evaluation is investigated in this study. SSG and DCP survey data of natural earthen materials, industrial by-products, chemically stabilized soils, and other materials from thirteen construction sites around the state of Wisconsin are presented along with their correlation with each other as well as with density and moisture content obtained from traditional tests. Weighted average of DCP penetration index (DPI) over depth of measurement is employed to obtain a representative strength index of the material. This approach provided better correlations than the arithmetic average. The dependency of SSG stiffness and DPI strength index on dry unit weight and water content followed, in general, a pattern consistent with those in other research on stiffness and strength. A simple linear semi logarithmic relationship is observed between SSG stiffness and DPI. DPI weighted average over a DCP penetration depth of 152 mm yields the highest coefficient of determination and also yields a statistically significant relationship between the SSG stiffness and DPI for all materials except fly ash-stabilized soils. This depth is consistent with the significant depth of measurement for the SSG as shown in a previous study. The SSG and DCP provide a convenient means of assessing stiffness and strength of earthen construction materials in the field.
284 p.
Keywords: Correlation analysis; Density; Cone penetrometers; Construction sites; Subgrade materials; Strength of materials; Soil stabilization; Stiffness; Fly ash; Moisture content; Evaluation; Earthwork; Field tests; Industrial wastes; Index tests